Response of N P K and Varieties of Wheat to the Population of Perrobia Latens (Muller) - Doval, S L; Bohra, O P; Sharma, S K (Annals of Arid Zone, 2016)
Continuous menace to wheat crop by Petrobia latens Muller in western Rajasthan necessitated the study of varietal and manurial responses to this pest. The studies were under taken at Regional Station of Agricultural Research, Sumerpur with the latest promising varieties and recommended doses of N P K and it was concluded that nitrogen levels and varieties have distinct response to the population built up. Nitrogen levels were directely proportional to the population. S227 variety was found most responsive to this pest.